Human bocavirus infection as a cause of severe acute respiratory tract infection in children. (October 2015) - Moesker, F.M.; van Kampen, J.J.A.; van der Eijk, A.A.; van Rossum, A.M.C.; de Hoog, M.; Schutten, M.; Smits, S.L.; Bodewes, R.; Osterhaus, A.D.M.E.; Fraaij, P.L.A.
Abstract: In 2005 human bocavirus (HBoV) was discovered in respiratory tract samples of children. The role of HBoV as the single causative agent for respiratory tract infections remains unclear. Detection of HBoV in children with respiratory disease is frequently in combination with other viruses or bacteria. We set up an algorithm to study whether HBoV alone can cause severe acute respiratory tract infection (SARI) in children. The algorithm was developed to exclude cases with no other likely cause than HBoV for the need for admission to the paediatric intensive care unit (PICU) with SARI. We searched for other viruses by next-generation sequencing (NGS) in these cases and studied their HBoV viral loads. To benchmark our algorithm, the same was applied to respiratory syncytial virus (RSV)-positive patients. From our total group of 990 patients who tested positive for a respiratory virus by means of RT-PCR, HBoV and RSV were detected in 178 and 366 children admitted to our hospital. Forty-nine HBoV-positive patients and 72 RSV-positive patients were admitted to the PICU. We found seven single HBoV-infected cases with SARI admitted to PICU (7/49, 14%). They had no other detectable virus by NGS. They had much higher HBoV loads than other patients positive for HBoV. We identified 14 RSV-infected SARI patients with a single RSV infection (14/72, 19%). We conclude that our study provides strong support that HBoV can cause SARI in children in the absence of viral and bacterial co-infections.